Transcriptomic analysis reveals pathogenicity mechanisms of Phytophthora capsici in black pepper - Vijayakumar, Saranya; Saraswathy, Gayathri G.; Sakuntala, Manjula (Frontiers in Microbiology, 2024)
The devastating disease “quick wilt” or “foot rot” is caused by the oomycete Phytophthora capsici Leonian and is affecting the economically significant spice crop black pepper (Piper nigrum L.). The details on the mechanism of interaction of P. capsici with its host black pepper remain poorly understood, hindering efforts to enhance disease resistance. To address this knowledge gap, we conducted an RNA-seq analysis to investigate the gene expression profile of P. capsici infecting black pepper. Comparative transcriptome analysis between axenic culture, and early and late infection stages of P. capsici revealed a substantial number of differentially expressed genes. Our findings demonstrate the induction of metabolic pathways, signaling cascades, and crucial pathogenicity-related processes during infection of black pepper by P. capsici. Specifically, we observed orchestrated expression of cell wall-degrading enzymes, effectors, and, detoxifying transporters at different infection time points, implicating their roles in pathogenicity. The expression patterns of key pathogenicity-associated genes, including effectors, were validated using reverse transcription quantitative real-time PCR. The effectiveness of agroinfiltration-mediated transient expression in black pepper for functional studies of effectors is also demonstrated in this study. Overall, this study establishes a strong foundation for further studies elucidating the pathogenic mechanisms employed by P. capsici infecting black pepper and for developing effective disease management strategies. Future investigations building upon these findings are essential for advancing our understanding of this pathosystem and for implementing targeted approaches to mitigate black pepper foot rot.